KETERWAKILAN PEREMPUAN DI DPRD KABUPATEN BENGKALIS PERIODE 2024-2029 - Delvi, Jeni; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
ABSTRACT Democracy guarantees equal rights for every citizen to be involved in politics. Women's representation is an important component in a country, especially in the legislative institution. In accordance with Law Number 7 of 2023 concerning General Elections, women's representation in legislative elections should have the same rights as men's representation and does not need to use the "at least" 30% limit. Women's representation in the Bengkalis Regency DPRD is still relatively low, therefore this study aims to describe the factors causing the low representation of women in the Bengkalis Regency DPRD for the 2024-2029 period. This study uses a qualitative approach method with a descriptive research type. The location of the study is in the Bengkalis Regency DPRD. Data collection techniques through interviews and documentation. Data analysis refers to the Theory of Asmaeny Azis regarding the factors causing low female representation in the DPRD which consists of four indicators, namely the Election System, the Role of Political Parties, Cultural Acceptance, and the Quality of Human Resources. The results of the study show that the low representation of women in the Bengkalis Regency DPRD ffor the 2024-2029 period is caused by several main factors. The formal open proportional election system provides equal oppurtunities for man and women, however, in reality, this election system makes it difficult for women to compete. The role of political parties has also not been fully maximized, parties in nominating women only fulfill the 30% quota. Malay culture in Bengkalis Regency is relatively open to women, even its leader is a woman, but patriarchal views and the dominance of masculinity remain challenges for women. With this research, it is hoped that there will be better changes made by the government, political parties, society, women, and women’s organizations so that women’s representation in the DPRD can be greater. Keywords: Representation, Women, Legislature.